WAS-GN: Web-based Appointment System with GSM Network - Abd Wahab, Mohd Helmy; Ooi, Lee Lee; Abdul Kadir, Herdawatie; Johari, Ayob; Abdul Mutalib, Ariffin; Mohamad Mohsin, Mohamad Farhan; Mohd Sidek, Roslina; A., Noraziah (Advanced Institute of Convergence Information Technology Research Center, 2011)
This paper presents a new way of online communications through mobile to web that helps students and lecturers to be always aware of appointments no matter where they are. It contributes to the teaching and learning process, in which communication is made easy using short messaging system (SMS) technology which is called Web-based Student Appointment System with GSM Network (WAS-GN).It starts with examples of previous success stories of the implementation of SMS in many areas.The objectives of the paper are to discuss about the hardware and software requirement, and integrate them to be measured in terms of functionality. The research method is outlined next, and some discussions over current outcomes of the research are addressed.The prototype of WAS-GN is successfully implemented using SMS technology.Briefly, results show that WAS-GN is able to solve the appointment-making problem.